150 ProBNP glycosylation of threonine 71 is increased with obesity in patients with heart failure. (13th January 2020) - Lewis, L; Raudsepp, S D; Yandle, T G; Frampton, C M; Richards, A M; Prickett, T C R; Doughty, R; Pemberton, C J
Abstract: Funding Acknowledgements: The National Heart Foundation of New Zealand Background: Heart failure (HF) is a leading cause of morbidity and mortality worldwide. Plasma levels of B-type natriuretic peptide (BNP) or its amino terminal congener (NT-proBNP) are used for HF diagnosis and risk stratification. Circulating levels of both BNP and NT-proBNP are reduced by obesity and this phenomenon is one of the key weaknesses of the diagnostic performance of the natriuretic peptides in HF. Formation of BNP from enzymatic cleavage of proBNP1-108 between residues 76 and 77 by corin and/or furin is influenced by the degree of proBNP glycosylation, therefore we investigated the relationship between proBNP glycosylation, plasma NT-proBNP and body mass index (BMI) in HF patients. Methods: Three assays were developed to distinguish between total proBNP (glycosylated plus non-glycosylated proBNP), proBNP not glycosylated at threonine 71 (NG-T71) and proBNP not glycosylated in the central region (NG-C). Intra and inter-assay CVs were <15%, limits of detection were <2 pmol/L and samples diluted in parallel. Results: Applying these assays and an NT-proBNP assay to plasma samples from 106 healthy volunteers and 238 patients with HF determined that concentrations (median(IQR)) of proBNP, NG-T71 and NT-proBNP were greater in HF patients compared to controls (24.9 (3.6-55), 9.4 (1.5-21) and 212 (104-409) pmol/L vs 3.0 (1.5-19), 3.0 (1.5-14.5) and 4.7 (2-8) pmol/L respectively, all p < 0.012). NG-C was undetectable in most samples. ProBNP levels in HF patients with BMI above and below 30 kg/m2 were not different (21.9 (2.6-70) pmol/L and 25.7 (3.9-53) pmol/L respectively, p = 0.85), whereas HF patients with BMI > 30 had lower NT-proBNP and NG-T71 levels (121 (64-248) and 3 (1.5-16) pmol/L verse 271 (178-486) and 13.5 (1.5-24.2) pmol/L respectively, p < 0.003) and higher proBNP:NT-proBNP and proBNP:NG-T71 ratios (p = 0.001 and p = 0.02 respectively) than those with BMI < 30. Discussion and Conclusion: Using three new assays specific for different glycosylated forms of proBNP we have shown that the processing of proBNP is dysregulated in heart failure compared to controls due to increased glycosylation at threonine 71 of proBNP. Obese patients with HF have even greater dysregulation, demonstrated by decreased concentrations of proBNP that is not glycosylated at T71 (NG-T71), and concomitant decreases in NT-proBNP. Thus, we have shown for the first time that increased BMI is associated with increased proBNP glycosylation at T71 in patients with heart failure. Glycosylation-induced impairment of proBNP processing explains, at least in part, the reduction in plasma concentrations of B-type cardiac natriuretic peptides observed in obesity. Using these assays to evaluate the proBNP profile of larger patient cohorts will further develop understanding of the relationships between BNP production, BMI and heart failure pathogenesis, which would be expected to lead to increased diagnostic performance.